Driven Clinical Decision Support for Early Detection of Sepsis in Resource - Chalidabhongse, Alissara; Anzari, Ahmad; Shrestha, Seesuriyachan (International Journal of Clinical Inventions and Medical Sciences (IJCIMS), 2025)
Sepsis remains a leading cause of morbidity and mortality worldwide, with disproportionately high burdens in low- and middle-income countries (LMICs) such as Thailand. Conventional clinical scoring tools, including qSOFA, often demonstrate limited accuracy in early sepsis detection, particularly in resource-constrained environments. This study addresses the urgent need for reliable, scalable, and interpretable predictive models by evaluating the performance of machine learning specifically Random Forest (RF) using hospital datasets from both tertiary and district hospitals in Thailand. The findings reveal that the RF model significantly outperformed logistic regression and qSOFA, achieving an AUROC of 0.89 and AUPRC of 0.76 in tertiary hospitals, and maintaining strong accuracy (AUROC 0.83, AUPRC 0.69) in district hospitals where fewer variables were available. Feature importance analysis highlighted systolic blood pressure, respiratory rate, oxygen saturation, and WBC count as the most influential predictors, aligning with established sepsis pathophysiology. Crucially, the model’s interpretability enhanced clinician trust and facilitated its potential integration into Thailand’s Universal Coverage Scheme and Health Data Center. These results demonstrate that lightweight, interpretable AI solutions can improve diagnostic accuracy and healthcare equity in LMIC settings. Thailand’s experience provides a transferable model for broader global health applications, illustrating how AI can support early sepsis detection, reduce mortality, and strengthen national health system resilience.